Countering covid-19 : case studies in crisis response - De Jesus, Edilberto C.; Dayrit, Manuel M.; Baysic, Ivyrose S. (Quezon City, Philippines : Bughaw, 2021)
The enormity of the COVID-19 pandemic urgently calls for a proactive and strategic response from across all sectors at all levels: global, national, and local. Countering COVID-19: Cases in Crisis Response, with its wide range of essays, makes the case for a coordinated and truly whole-of-society approach to contain, adapt to, and overcome the pandemic while laying bare preexisting systemic and structural inequalities. There is no other more critical time to confront these than now.
Part One. Public Health Policy and the Pandemic -- Part Two. Sectoral Concerns -- References -- About the Authors -- Index.
Includes bibliographical references and index.
Keywords: COVID-19 PANEDEMIC, 2020 -- PHILIPPINES; COVID-19 (DISEASE) -- GOVERNMENT POLICY -- PHILIPPINES